Statistical Analyses for language Assessment - Bachman, Lyle F. (Cambridge University Press, 2004)
The assessment of language learners is having a growing impact in English language teaching and applied linguistics. A formal evaluation of students' writing abilities is important for language teachers in order to assess the pedagogical needs of their students. While there has been a considerable body of work undertaken on assessing the writing abilities of native speakers, the issues surrounding the assessment of second language learners' writing abilities are still emerging. At present, no one volume has explored these issues and their implications for language teaching practitioners wishing to evaluate their students' writing. This book outlines in an accessible manner the major tenets of research in the field and provide language teachers with guidelines to design and develop suitable listening assessment tasks for their students.